Social Values in Horse Racing Culture: Case Study of Boal Village, Sumbawa Besar District - Nurwahyuni Nurwahyuni; Mohammad Liwa Irruba’i; Nazala Noor Maulany (STKIP Taman Siswa Bima, 2023)
The purpose of this research is to find out the social values contained in the horse racing tradition. The author took a case study in the Boal Village area, Empang District, Sumbawa Regency. The method used was descriptive research with a qualitative approach. The data collection methods used were observation, interview, and documentation. Then the data found were analyzed using the Miles and Huberman model (1984), including: data collection, data reduction, data display, and conclusion drawing. The results showed that the tradition existed before Indonesia's independence and is still taught from generation to generation until now. The horse racing tradition in Boal Village is a tradition played to celebrate the rice harvest and the anniversary of Boal Village. This tradition is one of the traditions that is arguably quite extreme because in the implementation of this tradition there are little jockeys who act as horsemen so that many argue that this tradition causes broken bones or the like, but it can be seen that until now the players who carry out this tradition are still fresh and fit until now. The social values contained in this tradition include the value of togetherness or mutual cooperation, the value of friendship, and the value of solidarity, the value of sportsmanship, and the economic value contained in horse racing culture.